Tissue culture studies of sinningia speciose / Nurul Aina Ismail and Marlina Mohd Mydin - Ismail, Nurul Aina; Mohd Mydin, Marlina (2012)
Diseases were a frequent problem that occurred in the natural environment. Sinningia speciosa may develop root rot from overwatering. Leaves may be damaged by excessive watering and therefore watering must be avoided from the foliage part. Mites and trips were the insect and pest that related to this species. By the aid of tissue culture technique, all of these problems can be avoided. The objective of this study was to evaluate the best proliferation of different explants of Sinningia speciosa on various combinations of plant growth regulators. This project also aimed to select the best shoot proliferation and rooting medium to produce complete plantlets of Sinningia speciosa via in vitro culture technique. Generally, the aim of. this study was to develop a micropropagation protocol that could maintain a mass production and continuous supply of Sinningia speciosa propagules to fulfill the market demand. In this study, leaves had been recognized to be the best explants in micropropagation of Sinningia speciosa. This explant showed an indirect regeneration pathway by obtaining shoots from the intermediary callus. From the micromorphological study using scanning electron microscope (SEM), the stomata of in vivo leaves were larger than in vitro leaves. There were also more trichomes located on in vivo plants compared to in vitro leaves and their sizes were longer. The plants propagated through tissue culture techniques did not show any morphological abnormalities when compared to the original or parent plants. The best medium for shoot proliferation of this ornamental plant was MS basal medium supplemented with 1.0 mg/l NAA and 1.5 mg/l BAP. The highest number of shoots per explants was obtained from leaves explants by using this optimal medium (6.3 ± 1.3). The healthy young shoots were induced to form roots in hormone-free MS basal media. Complete in vitro plantlets were acclimatized successfully in the natural environment.